Toward Composite Pain Biomarkers of Neuropathic Pain—Focus on Peripheral Neuropathic Pain - Diaz, Monica M.; Caylor, Jacob; Strigo, Irina; Lerman, Imanuel; Henry, Brook; Lopez, Eduardo; Wallace, Mark S.; Ellis, Ronald J.; Simmons, Alan N.; Keltner, John R. (Frontiers in Pain Research, 2022)
Chronic pain affects 10–20% of the U.S. population with an estimated annual cost of 600 billion, the most significant economic cost of any disease to-date. Neuropathic pain is a type of chronic pain that is particularly difficult to manage and leads to significant disability and poor quality of life. Pain biomarkers offer the possibility to develop objective pain-related indicators that may help diagnose, treat, and improve the understanding of neuropathic pain pathophysiology. We review neuropathic pain mechanisms related to opiates, inflammation, and endocannabinoids with the objective of identifying composite biomarkers of neuropathic pain. In the literature, pain biomarkers typically are divided into physiological non-imaging pain biomarkers and brain imaging pain biomarkers. We review both types of biomarker types with the goal of identifying composite pain biomarkers that may improve recognition and treatment of neuropathic pain.